Posterior Reversible Encephalopathy Syndrome in an Adolescent with Acute Poststreptococcal Glomerulonephritis - Doğan, Çağla Serpil; Aksoy, Gülşah Kaya; Kutluk, Muhammed Gültekin; Özkan, Mehmet Burak (Journal of Pediatric Neurology, 2020)
Posterior reversible encephalopathy syndrome (PRES) is a rare but severe complication of acute poststreptococcal glomerulonephritis (APSGN) in children. A 13-year old boy was diagnosed with APSGN based on clinical, laboratory, and renal biopsy findings. On the third hospital day, his blood pressure (BP) was 130/80 mm Hg on antihypertensive and diuretic treatment. He then developed confusion, blurry vision, and changes in speech and behavior. Over the next few hours, his BP increased to 160/90 to 170/90 mm Hg (99th percentile, 135/90 mm Hg). Magnetic resonance imaging of the brain revealed prominent hyperintensities in the right temporal, right temporo-occipital, and right parieto-occipital gray, and white matter on T2-weighted and fluid-attenuated inversion recovery images, compatible with PRES (posterior reversible encephalopathy syndrome). Electroencephalography showed generalized epileptiform activity. After treatment with anticonvulsant and additional antihypertensive medications, his clinical symptoms and neuroimaging findings were resolved. Posterior reversible encephalopathy syndrome should be considered in the differential diagnosis of patients with APSGN developing sudden neurological symptoms without severe increases in BP.
Keywords: acute poststreptococcal glomerulonephritis; adolescent; posterior reversible encephalopathy syndrome